(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The efficient and environmentally friendly synthesis of next-generation high-temperature superconducting (HTS) materials represents one of the most pressing challenges facing contemporary science and industry. When conventional furnaces are employed, the synthesis process requires significant energy consumption and results in the release of harmful carbon emissions into the atmosphere, thereby reducing both the economic and ecological efficiency of the process. From this perspective, the use of concentrated solar energy in the Large Solar Furnace (Parkent) provides a promising approach for the synthesis of HTS materials [1]. This method not only reduces energy expenditures but also minimizes environmental impacts, making it a “green technology”.